Pengaruh Pelatihan, Kompetensi, dan Penempatan Karyawan terhadap Motivasi Kerja Karyawan - Herlina, Tati; Dewi, Rosmala; Anisa, Mutiara (Universitas muhammadiyah palembang, 2022)
Competition in today's increasingly competitive business world will lead to high competition in all fields, it is important for companies to use human resources who have an awareness of their responsibilities to work better and more optimally. Employees need work motivation that is in accordance with their wishes in order to achieve company goals and desired results. Factors that can influence work motivation are by providing training, increasing employees’ competence and placement in accordance with the demands of the position. The purpose of this study was to determine the influence of training, competence and placement on employees’ motivation at PT. Semen Baturaja (Persero) Tbk either partially or simultaneously. The data analysis method used in this research is Multiple Linear Regression Analysis.The results of the partial (individual) hypothesis test analysis showed that training had a significant influence on work motivation, competence had a significant influence on work motivation and placement had a significant influence on work motivation. While the results of the analysis of hypothesis testing simultaneously (together) it was found that there was a significant influence between training, competence and placement on employees’ motivation at PT. Semen Baturaja (Persero) Tbk.